Comparison of Usability Level of E-Commerce Websites of Pakistan - Madiha Qadir; Adnan Ali (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Usability denotes to approaches for refining the ease-of-use in the application design. Online free classified shopping websites “daraz.pk” and “Homeshopping.pk” are among the top five online stores in Pakistan. It is important for the realization of online business that the structure of online shopping websites should be effective and efficient. The study aimed to compare the level of usability of both shopping websites in the form of Efficiency, Satisfaction and Effectiveness. It was found that e-commerce website which has higher usability level get more re-accessed probability. Two different evaluation methods were used: User testing and the quick and dirty method. Total 10 users have participated in this study to answer the questioners for satisfaction using the quick and dirty method. Then eight users were taken randomly to check the efficiency and effectiveness of both websites using user testing. The user testing of daraz.pk and Homeshopping.pk established that daraz.pk has greater efficiency as compared to Homeshopping.pk, but Homeshopping.pk have higher usability in term of effectiveness.